Spontaneous rupture of an intratumoral pseudoaneurysm in a giant renal angiomyolipoma - Abdul Malik, Mawaddah; Tharek, Anas; Kairuddin, Faizal Firdaus; Hui, Soo Tze; Ibrahim, Idris; Zakaria, Mohd Hazeman; Mohd Yaakob, Mohd Naim (The Interventionalist Journal, 2022)
We reported a rare case of a spontaneous rupture of an intratumoral pseudoaneurysm in a giant renal angiomyolipoma of a 52-year-old lady. The initial presentation was a sudden onset of right hypochondriac pain, nausea, and vomiting. CT scan revealed large heterogenous exophytic enhancing mass with mixed solid and fat density within, arising from the right kidney likely represent a giant right renal angiomyolipoma. There is associated right perinephric hematoma and active bleeding within the mass. No features suggestive of tuberous sclerosis. Subsequent right renal angiogram revealed a pseudoaneurysm of an inferior segmental right renal artery and emergency embolization was done with successful obliteration of the aneurysmal sac and devascularization of the mass.